Management of Refractory Posterior Epistaxis by Sphenopalatine Artery (SPA) Cauterization - Pradhan, B (Nepalese Journal of ENT Head and Neck Surgery, 2011)
Keywords: Epistaxis; Sphenopalatine artery; endoscopic surgery DOI: 10.3126/njenthns.v1i1.4727 Nepalese J ENT Head Neck Surg Vol.1 No.1 (2010) p.3-5